Relational communication - Anton Kolotilin; Hongyi Li (Theoretical Economics, 2021)
We study a communication game between an informed sender and an uninformed receiver with repeated interactions and voluntary transfers. Transfers motivate the receiver's decision-making and signal the sender's information. Although full separation can always be supported in equilibrium, partial or complete pooling is optimal if the receiver's decision-making is highly responsive to information. In this case, the receiver's decision-making is disciplined by pooling states where she is most tempted to defect.
Keywords: C73; D82; D83; 330; Strategic communication; relational contracts